SiO v = 1 J = 5 → 4 Maser Emission from the Root of the “Water Fountain” Source W 43A - Hiroshi Imai; Takeshi Hoshino; Daniel Tafoya; José F. Gómez; Jun-ichi Nakashima; Gabor Orosz (The Astrophysical Journal)
We report here the first mapping of SiO v = 1 J  = 5 → 4 maser emission toward the “water fountain” source W 43A in order to explore the central stellar system driving the collimated, bipolar, fast jet. The maser source has a systemic line-of-sight velocity consistent with that of CO J  = 2 → 1 emission tracing the jet within ∼2 km s ^−1 but a velocity gradient opposite that of the jet. The dynamical center of the maser source is located within ∼10 mas (or ∼20 au) of the brightness peak of the central 1.3 mm continuum emission. The spatiokinematic properties of the SiO J  = 5 → 4 and J  = 1 → 0 masers suggest that they are associated with the root of a slow (10 km s ^−1 < V _outflow  << 100 km s ^−1 ) outflow with a large opening angle, and the central stellar system is contained within the inner maser region (∼20 au) during a possible common-envelope evolution.